2007
DOI: 10.1111/j.1365-2796.2007.01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Two SNPs in the promoter region of the CTLA‐4 gene affect binding of transcription factors and are associated with human myasthenia gravis

Abstract: Abstract. Wang XB, Pirskanen R, Giscombe R, Lefvert AK (Shanghai University of TCM, Shanghai, China; and Karolinska University Hospital and Karolinska Institutet, Stockholm; Sweden). Two SNPs in the promoter region of the CTLA-4 gene affect binding of transcription factors and are associated with human myasthenia gravis. J Intern Med 2008; 263: 61-69.Objectives. The molecular mechanisms underlying the regulation of the CD152 (CTLA-4) gene are largely unknown. Two single nucleotide polymorphisms (SNPs) located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…It has been shown that there may be a correlation between CTLA4 gene variants and alternative splicing (39). The expression of alternatively spliced flCTLA4 and sCTLA4 isoforms are influenced by the CTLA4 5 0 -upstream regulatory region and 3 0 -untranslated region gene polymorphisms (37,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that there may be a correlation between CTLA4 gene variants and alternative splicing (39). The expression of alternatively spliced flCTLA4 and sCTLA4 isoforms are influenced by the CTLA4 5 0 -upstream regulatory region and 3 0 -untranslated region gene polymorphisms (37,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The noncoding region variants of CTLA4 gene may result in abnormal alternative splicing. It has been shown that the noncoding region SNPs of CTLA4 that present in the 5 0 -upstream regulatory region may cause abnormal alternative splicing and affect gene expression; hence, they may be associated with disease susceptibility (39).…”
Section: Discussionmentioning
confidence: 99%
“…A third generation human haplotype map catalogues from 1.3 to 4.1 million SNPs depending on ethnicity (Altshuler et al 2010). Polymorphisms within gene promoter regions can have profound effects on transcriptional efficiency of genes (Blank et al 2005;Myers et al 2007;Wang et al 2008) and may contribute to disease susceptibility of complex inherited traits. For example, a SNP in the interleukin-1 promoter region was reportedly associated with rheumatoid arthritis (Harrison et al 2008) and an E-cadherine160 C/A promoter polymorphism was associated with increased susceptibility and altered disease progression of pancreatic carcinoma in Chinese patients (Fei et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The first of these reports was made by Yanagawa et al (1995), who found a significant association between variation in the (AT) dinucleotide repeat within the 3'-untranslated region of the CTLA-4 gene and the presence of Grave's Disease (GD). Subsequent to these findings, many others have reported associations between SNPs within and around the CLTA-4 region and rheumatoid arthritis (Lei et al, 2005), celiac disease (Hunt et al, 2005), type I diabetes (Jung et al, 2009), myasthenia gravis (Wang et al, 2008) and autoimmune pancreatitis (Chang et al, 2007). Furthermore, the CTLA-4 gene has also been implicated in other autoimmune disorders like Hoshimoto's Thyroiditis (HT) (Kotsa et al, 1997), Addison's disease (Vaidya et al, 2002) and Multiple sclerosis (Kouki et al, 2000).…”
Section: Discussionmentioning
confidence: 98%